Performance-based strategy : tools and techniques for successful decisions - Fairbanks, Steve; Buchko, Aaron A. (Emerald Publishing Limited, 2018)
Executives in todays business environment have never been busier. Time constraints are ever present. Resources are strained. Strategic planning constantly competes with the tactical demands of running an organization. To make matters worse, most organizational leaders, when confronted with the need for strategic planning, have no idea about how to go about it. They have plenty of knowledge and information about the organization and their situation, but no effective tools to analyze their thoughts, to make decisions that will lead to effective strategies, and most importantly, to create a plan ofaction. In 'Performance Based Strategy', Steve Fairbanks and Aaron Buchko offer a practical set of simple, productive tools that will enable leaders to develop effective strategies. The bookoffers tools that have been tested in small, medium, and Fortune 100 companies, with for profit and not-for-profit organizations, and across a breadth of industries,such as manufacturing, health care, banking, distribution, transportation, government, and charities, among others. The authors have used these tools as insiders to turn around companies, and as outsiders in advisory and board roles. When properly applied, the strategies offered here enable leaders to see their situations and organizations in new ways. Managers will be able to present information in a way that everyone in the organization will understand. Executives can provide a sense of direction that will provide a framework for decision making that will give guidance to people. Above all, applying these tools will enable managers to improve their firms performance.